148 A Chair at the Table: A Scoping Review of the Participation of Refugee Adults and Youth in Healthcare Research and Policy Design. (29th October 2021) - Kaur, Pardeep; Minhas, Ripudaman; Filler, Tali; Torabi, Nazi
Abstract: Primary Subject area: Global Child and Youth Health Background: The current refugee crisis is described as the largest humanitarian crisis of all time. Refugees often face psychosocial complexity and multi-dimensional healthcare needs. Community-Based Participatory Research (CBPR) methods have been previously employed successfully in designing health programs for refugee children, youth and their families, and in building strong research partnerships in refugee communities. Objectives: To review the evidence in the involvement of refugee adults, youth and children in CBPR processes. Design/Methods: A scoping review was performed, using Arksey & O'Malley's methodological framework. A literature search in Medline, PubMed, PsycINFO, CINAHL, Embase and Scopus for articles published until August 2020 was conducted. Articles were included if they focused on CBPR or Participatory Action Research as the methodological framework, had refugee involvement and discussed healthcare and health policy. Data extracted included ethno-racial data, country of origin, purpose of CBPR, refugee CBPR involvement and its influence on health care research and policy. Results: 4125 articles were identified in the database searches. After removal of duplicates, 2077 articles underwent title and abstract review by two authors, yielding a kappa-statistic of 0.85. Fourteen studies were included in the final analysis. Of these, 35.7% (5/14) included refugee children/youth in their CBPR methods. The purpose of the CBPR methods for 60% (3/5) of the articles focused on mental health promotion-related strategies. The other 40% (2/5) of articles focused on reproductive health. Eighty percent (4/5) of the studies included refugees in the inception of the research problem and in knowledge translation efforts, whereas none were involved in seeking funding. All studies included refugee participants in the study design and engaging community/recruitment. However, there were varying degrees of involvement of refugees in the data analysis (40%, 2/5), knowledge translation (40%, 2/5) and scale up (20%, 1/5). All studies did not distinguish between the level of CBPR involvement of children and adolescents. Conclusion: There is scarce literature describing the involvement of refugee children, youth and their families in research. CBPR has been identified as a methodology with the potential to make substantial contributions to improving health and well-being in traditionally disenfranchised population groups. As the needs of refugee communities are so diverse, efforts should be made to include refugees in all stages of the research process. This scoping review demonstrates that levels of involvement in CBPR processes amongst refugee children, youth and adults may not be differentiated, and as such, may conflate their needs and experiences. Barriers to full participation in research processes should be examined further in order to eliminate health disparities and build capacity amongst refugee communities.